Government Spending asymmetric shocks in Algeria: Are the budget and current account deficits twins? - Meryem Gadiri; Mohammed Mekidiche (Journal of North African Economies, 2025)
This paper provides new evidence of the existence of the “twin deficits” in Algeria. We apply the Nonlinear Autoregressive Distributed-Lag approach to investigate the asymmetries in government spending shocks that can be occur the twin deficits, using time series data over the period 1990 to 2020. The results suggest that the budget and current account deficits appear to be twins in our analysis, in sense the government spending shocks that raise the budget deficit lead to persistent current account deficits for long-term. However, the real exchange rate shocks lead to a current account deficit in the short-term, While, the twin deficits hypothesis remains insufficiently ambiguous.